Impact of Critical Success Factors on Project Success Through the Mediation of Knowledge Creation - Naseer, Saira; Abbass, Kashif; Asif, Muhammad; Hashmi, Hammad Bin Azam; Naseer, Sidra; Achim, Monica Violeta (Frontiers in Psychology, 2022)
Several factors affect health project success. This research aims to examine the impact of critical success factors on health project success and show how the essential factors of success interact with knowledge creation to impact health project success. The self-administered questionnaire was distributed to collect data from 246 managers, supervisors, and zonal supervisors of DHQ Attock and PIMS Islamabad. The analysis was done using Smart PLS to understand the effect of exogenous variables over endogenous variables and the impact of mediating variables between two constructs. The results show that all critical success factors (MGTRF, DRF, CRF, PMRF, CLRF) mediate the association between essential factors of success and project success. In contrast, explicit knowledge creation does not mediate the relationship between critical success factors and project success. This study intends to expand the theoretical understanding of process improvement by providing practical insights into the impact of strategies used by project managers to develop new knowledge by capturing explicit and implicit information. This study also reinforces past findings and increases awareness about using knowledge creation to gain a competitive advantage in the health sector.